FEATURES OF THE DISTRIBUTION OF HLA- ANTIGENS AMONG PEOPLE OF THE UZBEK NATIONALITY IN THE SAMARKAND REGION - G. A. Dushanova; F. S. Nabiyeva; G. O. Rahimova (International Journal of Innovations in Engineering Research and Technology, 2023)
The study of the HLA genetic profile of the population was carried out using the most complete set of modern HLA typing reagents. For the first time, the study of the HLA phenotype was carried out for a wide range of alleles of the A, B and DR loci, separately among the residents of the city and the village inhabiting the Samarkand region.